2009
DOI: 10.1038/eye.2009.23
|View full text |Cite
|
Sign up to set email alerts
|

Use of a mydriatic cocktail with a wick for preoperative mydriasis in cataract surgery: a prospective randomised controlled trial

Abstract: Purpose To investigate the efficacy of a standardised wick soaked in a mydriatic cocktail regimen and compare it with the pre-existing regimen of topical dilating drops. Design Prospective, two armed, randomised, double blind, parallel assignment efficacy study Participants In all, 150 eyes of 150 patients were dilated using the dilating cocktail regimen by using a Weck cell sponge. The control group comprised of 75 eyes of 75 patients dilated using the conventional mydriatic regimen. Interventions A specially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…This incidence is lower that in the largest prospective study (n = 167) published to date [10], however α1-ARA medication is only one of the many predisposing factors [29]. Iris billowing – a hallmark of IFIS – was found in similar percentage in the two tamsulosin treated group as in two previous studies [11,24]. …”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…This incidence is lower that in the largest prospective study (n = 167) published to date [10], however α1-ARA medication is only one of the many predisposing factors [29]. Iris billowing – a hallmark of IFIS – was found in similar percentage in the two tamsulosin treated group as in two previous studies [11,24]. …”
Section: Discussionsupporting
confidence: 51%
“…Previous studies indicated that the use of a wick pre-soaked in standard mydriatic and non-steroidal anti-inflammatory drugs was as effective or superior to the conventional repeated instillation of drops before cataract surgery in a mixed cohort [21-24]. …”
Section: Introductionmentioning
confidence: 99%
“…Sengupta et al . [21] had reported on the use of a mydriatic cocktail with a wick for preoperative mydriasis in cataract surgery. A standard-sized wick soaked for a minute in mydriatic cocktail regimen (equal parts of phenylephrine, cyclopentolate, moxifloxacin, and flurbiprofen) was placed in the inferior fornix for 45 min, and this was found to be superior to topical dilation with regard to size of dilation, cost, patient comfort, and compliance and the main benefit being reduction in nursing time to administer drops.…”
Section: Discussionmentioning
confidence: 99%
“…This process is time consuming, and it has also been shown that repeated instillation of drops may damage the corneal epithelium, which may cause patient discomfort and interfere with the visibility during surgery. 6 Therefore, additional methods for pupil dilation have been explored. Intracameral injection of mydriatic agents has been shown to be safe and effective, 7, 8 but was reported to be inferior to conventional topical mydriasis in several studies.…”
Section: Introductionmentioning
confidence: 99%
“…9, 10 Use of wicks saturated in mydriatic agents has been shown to be comparable to use of drops, but has been associated with an increased risk of conjunctival and corneal abrasions. 6, 11, 12 One recent study has reported the topical use of a gel containing phenylephrine, tropicamide, diclofenac, and lidocaine for topical anesthesia and mydriasis, which was found to achieve greater and more rapid pupil dilation compared with drops. It has been suggested that the greater efficacy is owing to the fact that the gel was retained in close proximity to the eye while the drops were cleared by the lacrimal system, and that the gel formulation provided additional permeability through the cornea.…”
Section: Introductionmentioning
confidence: 99%